Computational Fluid Dynamic Analysis of Turbo Cyclone and Intake Manifold Spacer on Honda Supra Fit - Sarjito; Sandhika Putra Pratama; Wijianto; Subroto (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2022)
The need for human mobility is constantly increasing over time, so the demand for vehicle production mass is still relatively high. A large number of conventional vehicle use makes the impact of dependence on fuel oil. This dependence is very threatening for various aspects. Increasing the combustion efficiency in the engine room is necessary. Turbo cyclone is an additional component applied to the intake manifold, which causes the originally linear inflow to rotate (swirl) and mix fuel with air more maximally in the combustion engine to increase the combustion efficiency. Recently, we fabricated and characterized turbo cyclone and intake manifold spacer to increase the combustion engine's performance. Turbo cyclone designed in two different blades with a degree 400 with an angle of inclination blade. Intake manifold spacer designed with 24 grooves with a 400 angle. A selected sample in this research is the Honda Supra Fit 125CC year 2006. In this study, to increase the combustion engine's performance, we applied the 3-blade turbo cyclone and 4-blade turbo cyclone in the air filter. We applied an intake manifold spacer between the combustion engine and carburetor. Computational Fluid Dynamic (CFD) of turbo cyclone and intake manifold spacer is shown the changing in velocity, pressure, and turbulence intensity. The specific result shown in 4-blade turbo cyclone with change in velocity is 0.14009 m/s, with pressure drop -0.04582 Pa, and the change of turbulence intensity value is 2.44536 % explain that the turbulence condition is a medium-turbulence case. The unspecific result in the intake manifold spacer shows only a change in velocity 0.26269 m/s with a pressure drop of only -0.00673 Pa, which means the inner flow profile is almost linear. It proves from turbulence intensity value only 0.41247 % explain that internal air-flow in low-turbulence flow condition. Based on turbulence case from turbulence intensity, it has shown increased performance in the medium-turbulence case. These results suggest that turbo cyclone and intake manifold spacer can increase the performance of combustion engines.